"Sinto que nossa geração precisa repensar o trabalho": processo de significação do trabalho para a geração Z no Brasil - Silva, Paulo Duque Pereira da (2020)
Although it has been assuming new formulations and undergoing transformations in contemporary society, working is conceived as a fundamental category of the human condition, admitting it as central and constitutive of subject's life. It is expressive to understand how working is perceived and experienced by different groups. Therefore, the main objective is composed of two cores: 1) to identify and analyze the meanings of working and meaningfulness at working for Brazilian Generation Z workers, besides 2) propose a definition for "Working Significance Process" as an alternative to meaning and meaningfulness at work, such as contained in the literature. The study is characterized as applied and descriptive-exploratory, using the incorporated mixed methodology, in which the qualitative approach is integrated into a broader quantitative project, with the implementation in a single phase. Data were collected through a survey, with a structured questionnaire and incorporation of open questions to improve data analysis. The Inventory of the Meaning of Work and Meaningful Work Scale instruments were used to ascertain the meanings of working and meaningfulness at working for the Brazilian Generation Z members, as well as to evaluate the models present in the contemporary literature. A total of 210 young people between 18 and 25 years old from several Brazilian states participated in the survey, with greater predominance for participants of São Paulo. The results pointed greater convergence between the approaches of the meanings of working and a smaller for the meaningfulness at working. Among the meanings of working, young people associate working with learning, financial return, and independence. Regarding the meaningfulness at working, the quantitative method indicated greater appreciation and positive evaluation in the quality of working relationships, development, learning, and work utility, while qualitative analyses pointed to the interesting character of working, the social functions and beneficial actions to the society and others that it is allowed to undertake, as well as the identification with daily and professional practices, and the results arising from the work activity. A critique of the instruments as found in the literature was also performed, proposing the perspective of Socio-Historical Psychology as a theoretical-methodological alternative for a better understanding of the working significance process.